O uso de recursos educacionais digitais na prática pedagógica de professores dos anos iniciais do ensino fundamental - Cunha, Emanuelle do Nascimento Dias (2024)
Teacher professional development for the use of digital technologies has been a relevant topic both nationally and internationally. Over the years, several researches and initiatives have been developed with the purpose of improving teacher’s knowledge and practice in order to adapt them to rapid technological changes. Despite considerable advances, teacher training remains a topic in constant evolution, demanding continuous investigation and reflection on current policies and practices. This research investigates a teacher training process focused on the use of Digital Educational Resources (RED) by teachers who teach Portuguese Language and Mathematics in the early years of Elementary School. The object of study came from training for the employment of these RED. The research problem is guided by the following question: how do teachers incorporate Digital Educational Resources (RED) into their planning through contextualized training? Given this, the general objective is to: understand the contribution of training to the integration of Digital Educational Resources (RED) by teachers in the early years of elementary school in a school in the Municipal Public Network of Fortaleza. To meet this purpose, this work proposes the following specific objectives: a) Map teachers' knowledge and practice in relation to the use of digital resources before training; b) Analyze how training contributed to the integration of RED into teachers’ pedagogical practice; c) Investigate the challenges faced by teachers from the Municipal Public Network of Fortaleza after the introduction of RED in the activities carried out in the classroom. The locus of the research was a training process in a municipal public school in Fortaleza, Ceará, and the research subjects were 13 pedagogical teachers who participated in this training. Data collection instruments included questionnaires, field diaries of training meetings and classes and interviews. The results indicate that: 1) prior to training, only one teacher had experience in using digital technologies in teaching, despite the school having an innovation room with chromebooks. 2) Even during training, teachers began to incorporate RED into their pedagogical practices. 3) Teachers' pedagogical practices using RED were intensified at the end of training; 4) Pedagogical practices pointed to the autonomy of teachers who integrated RED and analogue materials into their planning in different ways; 5) Teachers pointed out several contributions of RED for their students, such as: expanding the repertoire of strategies, increasing engagement and improving learning; 6) The challenges for implementing RED in pedagogical practice are: lack of continuing training, lack of internet at school and lack of technical support team to use the technology. These results demonstrate that to expand the use of technologies in schools, policies that support teachers in their daily practices are necessary.